ANALYSIS OF LAGGED CORRELATION AND WAVELET COHERENCE BETWEEN PWV FROM GNSS AND RAINFALL IN THE SOUTHERN INDONESIA REGION - Barbarosa, Azhari
Rainfall is the main characteristic that describes the weather and seasons in Indonesia. There are many factors that can affect rainfall patterns, one of which is the monsoon which determines the timing of the dry season and rainy season in Indonesia. Monsoons affect the movement of water vapor in the atmosphere, which is often represented as Precipitable Water Vapor (PWV). To estimate the value of PWV, GNSS (Global Navigation Satellite System) is an alternative that is able to fulfill these needs with its high spatial resolution and temporal resolution. In this case, GNSS observations were made using InaCORS (Indonesia Continuously Operating Reference Station) which is spread across Indonesia. However, the current distribution of InaCORS has a dense distribution in the southern part of Indonesia. This is one of the reasons for the limitation of the research location. The researcher hypothesized that PWV and rainfall have a close relationship and are influenced by the movement of the monsoon. The methods used to explore this relationship are the lagged correlation (cross correlation) and wavelet coherence methods. These two methods can describe and quantify the relationship and show whether there is a time lag. The data used are InaCORS observation data as PWV data and GSMaP (Global Satellite Mapping of Precipitation) data as rainfall data. The results showed a pattern for correlation and time lag in southern Indonesia. The correlation value will decrease towards the east and the time lag value of 1 pentad is in parts of Central Java, Yogyakarta Special Region, and East Java. The phenomenon is due to the orographic influence and the movement of monsoon winds acting in the area. The correlation value also shows a pattern based on the monsoon movement, where the highest correlation is during the west monsoon and the lowest during the east monsoon. In addition, the wavelet coherence results show that the station samples in the Nusa Tenggara Islands have coherence values that are not as strong as the other station samples. This could be due to the weak west monsoon effect and the strong ENSO effect in the Lesser Sundas.